2012
DOI: 10.1177/1934578x1200700505
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Plant Origin of the Botanical Biomarkers of Mediterranean type Propolis

Abstract: Propolis is a honeybee product which bees produce by collecting resins from various botanical sources. The chemical composition of propolis is directly dependant on the availability of resinous plant materials in different geographic regions. This study was undertaken to evaluate the resinous plant sources used by bees to produce Mediterranean type propolis. Although this propolis type has already been the subject of numerous studies, its major botanical source had not yet been identified. In this study, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Examples of plant species that serve as botanical source for tropical propolis include Baccharis species, predominantly Baccharis dracunculifolia DC (Brazil, green propolis), Dalbergia species (Cuba, Brazil, Mexico, red propolis), 8 Clusia major and Clusia minor (Venezuela, Cuba), Macaranga tanarius (Pacific region), 9 Cistus species (Tunisia), Ambrosia deltoidea (Sonora desert [United States, Mexico]), Larrea nitida Cav. 14 The plant origin of the most widespread propolis types and their major constituents (vide infra) are shown in Table 1. 3,13 The plant origin of propolis is not always certain.…”
mentioning
confidence: 99%
“…Examples of plant species that serve as botanical source for tropical propolis include Baccharis species, predominantly Baccharis dracunculifolia DC (Brazil, green propolis), Dalbergia species (Cuba, Brazil, Mexico, red propolis), 8 Clusia major and Clusia minor (Venezuela, Cuba), Macaranga tanarius (Pacific region), 9 Cistus species (Tunisia), Ambrosia deltoidea (Sonora desert [United States, Mexico]), Larrea nitida Cav. 14 The plant origin of the most widespread propolis types and their major constituents (vide infra) are shown in Table 1. 3,13 The plant origin of propolis is not always certain.…”
mentioning
confidence: 99%
“…Mono-and sesquiterpenyl esters of substituted benzoic acids were also detected [ferutinin (38), teferin (39), 2-acetoxy-6-p-methoxybenzoyljaeschkeanadiol (40) and 2-acetoxy-6p-hydroxybenzoyljaeschkeanadiol (41)] ( Figure 4). [70] In 2012, [14] concluded that the diterpenic profile of the previous studied Maltese propolis was similar to the profile of the resin of Cupressus sempervirens and consider that cypress is the principal plant source of this propolis. Later on, [71] have reported totarol (36) to be the most abundant diterpenoid in Maltese propolis.…”
Section: Southern European Coastmentioning
confidence: 94%
“…Boisard et al [40,41] declared that phenolic acids esters [benzyl caffeate (12) and prenyl caffeate (13)] and flavonoids [pinobanksin-3acetate (4), pinocembrin (3), chrysin (2), and galangin (9)] were the most abundant constituents of French propolis. Caffeic acid (5), p-coumaric acid (6), ferulic acid (7) and isoferulic acid (14) were also detected in those propolis samples. The study of Chasset et al [42] was in concordance with [40,41] finding about the composition of French propolis, where they investigated propolis from different areas in France through high-performance thin-layer chromatography and mass spectrometry (HPTLC/MS).…”
Section: Southern European Coastmentioning
confidence: 94%
See 1 more Smart Citation
“…Amongst the propolis constituents, resin derived from plants provides the characteristics of texture, colour, and odour, as well as the complex chemical composition of the propolis and its biological activity. The chemical composition of propolis varies widely according to geographic and floristic factors (Bankova, de Castro, & Marcucci, 2000;Popova et al, 2012;Salatino, Fernandes-Silva, Righi, & Salatino, 2011).…”
Section: Introductionmentioning
confidence: 99%